Effect of initial concentration of chitosan on the particle size of chitosan nanoparticle - Ahmad Shapi'i, Ruzanna; Othman, Siti Hajar; Naim, Mohd Nazli; Kadir Basha, Roseliza (2018)
In this study, chitosan nanoparticle (CNP) was produced via ionic gelation process with varying initial concentration of chitosan (0.3, 0.6, 0.9, 1.2, 1.5, 1.8, and 2.1% w/v). The particle size of CNP was measured using dynamic light scattering (DLS) and transmission electron microscope (TEM). It was found that the particle size of CNP increased with the increase in initial concentration of chitosan. This was due to the agglomeration of the CNP that produced with high concentration of chitosan as proven from the TEM images. Fourier transmission infrared (FTIR) analysis revealed the peak of amide shifted from 1658 to 1635 cm-1, thus confirmed the formation of CNP. Energy dispersive X-ray elemental analysis (EDX) also revealed the presence of phosphorus in the CNP, thus confirmed the cross-linking of chitosan and sodium tripolyphosphate.